KENAKALAN REMAJA DI KOTA PADANGSIDIMPUAN DAN UPAYA PENANGGULANGANNYA - RISDAWATI SIREGAR (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2017)
The problem of this research was about the teenagers mischeaf in Padangsidimpuan, such as the entity, the caused factors, and the way to overcome. The purpose is to know the teenagers mischeaf in Padangsidimpuan, the caused factors of the teenagers mischeaf, and the way to overcome the mischeaf. It is done through qualitative research, and the informants were from BKKBN, the society prominent figure, religious figure, and teenegers in Padangsidimpuan. Besides, data also got from document of the police office and BKKBN. The result shows that the teenagers mischeaf is often happened in Padangsidimpuan, for instance free riders, free sexs, drugs, gambling, and leave out from school. The caused factors are family, school, environment, schoolmate, and electronic media. To overcome the problems, the parents have high responsibility. They must keep out their children, and give religious education. The parents must pay attention to control the children relationship and to fill their free time with useful activities. In addition, they should be as a model for their children. The other ways to overcome are from the school and government, they must do some activities to guide the students and the children to do the best things on order to avoid themselves from NAFZA and unhealthy of reproduction, such as by giving workshops, or explanation about the negative effects of free sex and NAFZA.